Pyruvate dehydrogenase kinase regulates macrophage polarization in metabolic and inflammatory diseases - Li, Chenyu; Liu, Chuanbin; Zhang, Junfeng; Lu, Yanyu; Jiang, Bingtong; Xiong, Huabao; Li, Chunxia (Frontiers in Immunology, 2023)
Macrophages are highly heterogeneous and plastic, and have two main polarized phenotypes that are determined by their microenvironment, namely pro- and anti-inflammatory macrophages. Activation of pro-inflammatory macrophages is closely associated with metabolic reprogramming, especially that of aerobic glycolysis. Mitochondrial pyruvate dehydrogenase kinase (PDK) negatively regulates pyruvate dehydrogenase complex activity through reversible phosphorylation and further links glycolysis to the tricarboxylic acid cycle and ATP production. PDK is commonly associated with the metabolism and polarization of macrophages in metabolic and inflammatory diseases. This review examines the relationship between PDK and macrophage metabolism and discusses the mechanisms by which PDK regulates macrophage polarization, migration, and inflammatory cytokine secretion in metabolic and inflammatory diseases. Elucidating the relationships between the metabolism and polarization of macrophages under physiological and pathological conditions, as well as the regulatory pathways involved, may provide valuable insights into the etiology and treatment of macrophage-mediated inflammatory diseases.